Limitations on ACI Code Minimum Thickness Requirements for Flat Slab - Abd Al-Zahra, Bilal Ismaeel; Alwash, Maitham; Baiee, Ameer; Shubbar, Ali A. (Civil Engineering Journal, 2021)
Reinforced concrete two-way flat slabs are considered one of the most used systems in the construction of commercial buildings due to the ease of construction and suitability for electrical and mechanical paths. Long-term deflection is an essential parameter in controlling the behavior of this slab system, especially with long spans. Therefore, this study is devoted to investigating the validation of the ACI 318-19 Code long-term deflection limitations of a wide range of span lengths of two-way flat slabs with and without drop panels. The first part of the study includes nonlinear finite element analysis of 63 flat slabs without drops and 63 flat slabs with drops using the SAFE commercial software. The investigated parameters consist of the span length (4, 5, 6, 7, 8, 9, and 10m), compressive strength of concrete (21, 35, and 49 MPa), the magnitude of live load (1.5, 3, and 4.5 kN/m2), and the drop thickness (0.25tslab, 0.5tslab, and 0.75tslab). In addition, the maximum crack width at the top and bottom are determined and compared with the limitations of the ACI 224R-08. The second part of this research proposes modifications to the minimum slab thickness that satisfy the permissible deflection. It was found, for flat slabs without drops, the increase in concrete compressive strength from 21MPa to 49MPa decreases the average long-term deflection by (56, 53, 50, 44, 39, 33 and 31%) for spans (4, 5, 6, 7, 8, 9, and 10 m) respectively. In flat slab with drop panel, it was found that varying drop panel thickness t2 from 0.25 to 0.75 decreases the average long-term deflection by (45, 41, 39, 35, 31, 28 and 25%) for span lengths (4, 5, 6, 7, 8, 9 and 10 m) respectively. Limitations of the minimum thickness of flat slab were proposed to vary from Ln/30 to Ln/19.9 for a flat slab without a drop panel and from Ln/33 to Ln/21.2 for a flat slab with drop panel. These limitations demonstrated high consistency with the results of Scanlon and Lee's unified equation for determining the minimum thickness of slab with and without drop panels. Doi: 10.28991/cej-2021-03091769 Full Text: PDF